Long-Term Effects Of Gadget Use On Children's Health - Siti Mardhatillah Musa; Juni Purnamasari; Murni Lestari; Hikmah Hikmah (Oshada, 2025)
Excessive use of gadgets in children has become an increasingly worrying issue in the digital era, especially because of its impact on physical, mental, and social health. Physically, excessive screen exposure can cause sleep disorders, progressive myopia, digital eye strain, and increase the risk of obesity due to a sedentary lifestyle. In addition, poor posture during gadget use contributes to musculoskeletal disorders such as neck and back pain. Mentally and socially, gadget dependence is associated with increased anxiety, depression, and attention disorders due to reduced direct social interaction and exposure to inappropriate digital content. The phenomenon of cyberbullying and social comparison in digital media can also lower children's self-esteem. To overcome these negative impacts, parental supervision and stricter regulation of gadget use are needed. Strategies such as limiting screen time, creating gadget-free areas, and encouraging alternative activities are important steps in balancing the use of technology. On the other hand, if used wisely, gadgets can be an effective learning tool. Therefore, a balanced and collaborative approach between families, schools, and governments is needed so that children can take advantage of technology without sacrificing their health and well-being